Informed consent in odontology. A theoretical-practical analysis - Palomer R., Leonor (Acta Bioethica, 2009)
In order to know more about the petition of informed consent in odontology, we realized a search of information in the database of SciELO and Pub Med, using the key words "informed consent", "odontology" and "autonomy". As a complement, in order to have information about the situation in Chile, a survey was sent to 40 dental surgeons in 3 dentalcenters belonging to the health network of the Pontificia Universidad Católica de Chile. It can be observed that there still exists disinformation in odontology in Chile relating to the purpose, implications and importance of an adequate process of informed consent in the dentist-patient relationship.